Identification of Novel Single-Nucleotide Variants With Potential of Mediating Malfunction of MicroRNA in Congenital Heart Disease - Liu, Wangkai; Cheng, Liangping; Chen, Ken; Wu, Jialing; Peng, Rui; Tang, Yan-Lai; Chen, Jinghai; Yang, Yuedong; Li, Peiqiang; Huang, Zhan-Peng (Frontiers in Cardiovascular Medicine, 2021)
Congenital heart defects (CHDs) represent the most common human birth defects. Our previous study indicates the malfunction of microRNAs (miRNAs) in cardiac neural crest cells, which contribute to the development of the heart and the connected great vessels, is likely linked to the pathogenesis of human CHDs. In this study, we attempt to further search for causative single nucleotide variants (SNVs) from CHD patients that mediating the mis-regulating of miRNAs on their downstream target genes in the pathogenesis of CHDs. As a result, a total of 2925 3’UTR SNVs were detected from a CHD cohort. In parallel, we profiled the expression of miRNAs in cardiac neural crest cells and found 201 expressed miRNAs. A combined analysis with these data further identified three 3’UTR SNVs, including NFATC1 c.*654C>T; FGFRL1 c.*414C>T and CTNNB1 c.*729_*730insT, which result in the malfunction of miRNA-mediated gene regulation. The dysregulations were further validated experimentally. Therefore, our study indicates that miRNA-mediated gene dysregulation in cardiac NCCs could be an important etiology of congenital heart disease, which could lead to a new direction of diagnostic and therapeutic investigation on congenital heart disease.